Peran Kerja Sama Perbankan Dengan Koperasi Unit Desa (KUD) Karya Baru Desa Teluk Tigo Kecamatan Cermin Nan Gedang Kabupaten Sarolangun - Nur Azila Fitria; Habriyanto Habriyanto; Agus Riandi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the role of banking cooperation with cooperatives and the obstacles to the role of banking cooperation with the Karya Baru village unit cooperative (KUD), Teluk Tigo Village, Cermin Nan Gedang District, Sarolangun Regency. This thesis uses qualitative research methods, the data sources used are primary and secondary data sources with data collection techniques and instruments through observation, interviews and documentation. The research results show that this cooperative collects funds from its members in the form of mandatory savings, principal savings and voluntary savings. However, in carrying out cooperative activities, the cooperative management has not yet collaborated between the bank and the cooperative. The role of banking in this case is simply a place to store money for the administrators of the Karya Baru Village Unit Cooperative (KUD) in Teluk Tigo Village. There are no mutual benefits provided by either the cooperative or the banking sector, so members continue to withdraw money/borrow money through the cooperative in cash. One of the factors supporting the achievement of the goals of a program is its implementation. If the implementation of a program is good and on target, then the program can also have an impact on society. However, in this case the obstacle faced by the cooperative management is the lack of understanding of the management so that the cooperative being run is not very optimal so that the community does not have confidence in its management.